DEEPFAKE IN ONLINE FRAUD CASES: THE HAZE OF ARTIFICIAL INTELLIGENCE’S ACCOUNTABILITY BASED ON THE INTERNATIONAL LAW - Davey, Orima Melati; Sauerwein, Levin (Sriwijaya Crimen and Legal Studies, 2023)
Artificial Intelligence (AI) is the science and engineering of intelligent machines, primarily through computer programs. AI consists of processes by human intelligence simulated through machine processes and is concerned with designing, developing, and implementing computer systems. One of them is Deepfake. Deepfake is a technology that uses data as an image/photo of a person’s face, which is part of personal data and potentially misused to commit crimes such as online loan fraud. The research discusses (1) the Benefits and Disadvantages of Artificial Intelligence in Human Lives, (2) the concept of accountability for deepfake artificial intelligence in online loan fraud according to international law and its application in Indonesia, and (3) the analysis of regulations and accountability of deepfake according to chaos theory. The research uses a legal-normative approach. Moreover, the research will examine legal principles, systematics, and comparative law in its application. The research illustrates that deepfake accountability as artificial intelligence in online loan fraud according to international law is described in the General Recommendation on the Ethics of Artificial Intelligence by The United Nations Educational, Scientific, and Cultural Organization (UNESCO). Meanwhile, the concept of accountability in Indonesia is seen in Human Rights and Data Privacy Violations. According to chaos theory, the analysis of Deepfake’s regulatory and accountability concept in international and national law leads to inconsistencies because it is only a recommendation, yet to be integrated, and still multidimensional.